The application of relationship marketing in the construction industry: Work in progress report - Davis, Peter (ARCOM, 2003)
Relationship Marketing (RM) embodies international, industrial and services marketing and in a business context is superseding traditional marketing theory. It is apparent from initial research into product and process industries that RM has the potential to provide construction organisations with significant benefits. These benefits include; enhanced ability to overcome problems, close coordination, process improvements; reduced risk associated with complex decision making and significant long-term value to prospective and existing clients. To determine a suitable research strategy for a PhD topic, a focus group was set up with construction industry stakeholders to discuss issues associated with RM. A brief description of the process and outcome leads to the conclusion of the merit in the research topic. A subsequent literature review formed the basis of quantitative questionnaires that were sent to a broad cross section of the Perth construction community. Interim results of the field study are presented and aligned with concurrent empirical studies of literature pertaining to RM. The final outcome provides a robust benchmark for construction organisations to consider that draws together contemporary best practice contract strategies and industrial and services marketing RM theory/research. In conclusion an insight into how RM thinking in business services marketing may guide strategic direction for construction organisations is provided.